From Rat to Human: Regulation of Renin-Angiotensin System Genes by Sry - Jeremy W. Prokop; Ingrid Kazue Mizuno Watanabe; Monte E. Turner; Adam C. Underwood; Almir S. Martins; Amy Milsted (International Journal of Hypertension)
The testis determining protein, Sry, has functions outside of testis determination. Multiple Sry loci are found on the Y-chromosome. Proteins from these loci have differential activity on promoters of renin-angiotensin system genes, possibly contributing to elevation of blood pressure. Variation at amino acid 76 accounts for the majority of differential effects by rat proteins Sry1 and Sry3. Human SRY regulated rat promoters in the same manner as rat Sry, elevating Agt, Ren, and Ace promoter activity while downregulating Ace 2. Human SRY significantly regulated human promoters of AGT, REN, ACE2, AT2, and MAS compared to control levels, elevating AGT and REN promoter activity while decreasing ACE2, AT2, and MAS. While the effect of human SRY on individual genes is often modest, we show that many different genes participating in the renin-angiotensin system can be affected by SRY, apparently in coordinated fashion, to produce more Ang II and less Ang-(1–7).